ELECTRONIC LEGAL CERTAINTY OF THE ROYA DEED OF ENCUMBRANCE - Rania Rania; Benny Djaja; Maman Sudirman (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The authority of a Notary is a distinct jurisdiction, grounded in Law Number 2 of 2014 Amendment to Law Number 30 of 2004 concerning the Position of Notary. The mortgage right, serving as collateral, is registered by the bank through a Notary/PPAT with the local National Land Agency. This process results in the issuance of a Deed of Mortgage Encumbrance (APHT) for the land used as collateral. Subsequent to the termination or deletion of the mortgage right, the note or mortgage right is electronically written off. The research problem is formulated as follows: What is the mechanism for electronic mortgage registration, and what is the legal certainty of electronic mortgage deeds? The electronic mortgage registration can be conducted either directly by the community or with the assistance of a Notary in their respective locations, facilitating the process for the community. The introduction of Electronic Mortgage Rights brings positive benefits to the community, banks/creditors, and PPAT, streamlining the mechanism for binding and registering mortgage rights, making it more efficient, faster, and cost-effective. Moreover, Regulation of the Minister of ATR/Head of BPN Number 5 2020 ensures legal certainty and protection for the public, particularly creditors. When executing a Roya Deed of Mortgage, the debtor must appear before a notary, ensuring legal certainty as authentic evidence of their actions, in accordance with Article 15 paragraph (1) of the Notary Position Law.